Expressão de genes codificantes para proteínas de choque térmico em sementes de linhagens de milho - Diogo Junior, Rubens (2018)
Among the proteins that confer the thermotolerance capacity to maize seeds, it stands out the heat shock proteins (HSP's), belonging to the class of dehydrins that, in turn, constitute the second LEA proteins group, recognized for their participation in the response to different kinds of stresses in plants. HSP's act in the assembly of multiprotein complexes, in the appropriate transport of proteins to their target subcellular compartment, in the control and signaling of the cell cycle, in the protection of cells against high temperatu re stress, and against an eventual apoptosis. In view of this, the objective of this work was to quantify the expression of genes coding for heat shock proteins in seeds of maize lineages with different tolerance levels at high drying temperatures. After r eviewing the literature, 37 genes coding for HSPs and for other proteins acting on high temperature response metabolism were selected, so for each gene a specific primer pair was designed. Seeds of ten maize lines, belonging to Geneseeds Recursos Genéticos Ltda® and pre-identified as contrasting with respect to tolerance to high drying temperatures, were multiplied and submitted to two drying treatments: 35º C and 50º C. After being submitted to the evaluation of the physiological quality, through the germination test, first count, cold test, and accelerated aging test, the genotypes were classified into two different groups: tolerant and non-tolerant to high applied drying temperature. Six contrasting inbred lines for this characteristic, three of each grou p, were submitted to a polymorphism analysis through the conventional PCR technique, using the 37 pairs of primers previously synthesized. Among these, ten showed some degree of polymorphism between the two groups of genotypes, evidencing some function in the metabolism of response to high drying temperatures. These ten pairs of primers, along with five other reference gene candidate primers, had their efficiencies tested through the Real Time PCR technique. Among these, three pairs of target genes primers met the required conditions: efficiency ranging from 80% to 100%, and single peak on the Melting curve. So then had their relative expressions calculated. It was observed that, after the application of the high drying temperature, the HSP 26 and HSP 70-74-B genes increased their expression levels in all the materials analyzed in both the tolerant and non -tolerant lineages. For the HSP 70-74-A gene, a different pattern of expression profile change was observed between control (drying at 35 ° C) and the high temperature treatment (drying at 50 ° C): their expression levels increased at the tolerante genotypes (L64 and L63), whereas in the non -tolerant materials (L30 and L57) this expression was reduced. It is inferred, therefore, that the expression of this gene is associated with the acquisition of thermotolerance in corn seeds. Thus, it is concluded that the 3 genes evaluated during all stages of these experiments have an effective participation in the metabolism of stress response by high drying temperatures .